Effect of Caribbean Water incursion into the Gulf of Mexico derived from absolute dynamic topography, satellite data, and remotely sensed chlorophyll a - Delgado, Juan Antonio (2019)
The dynamics of the Loop Current (LC) and the detached Loop Current eddies (LCEs) dominate the surface circulation of the Gulf of Mexico (GoM) and transport Caribbean Water (CW) into the gulf. In this work, 25 years (1993–2017) of daily satellite data are used to investigate the variability of these physical processes and their effect on chlorophyll a (Chl a) concentrations from 1998 to 2017, including temporal changes, mean differences, and regional concentration tendencies. The physical variables analyzed are absolute dynamic topography (ADT) and oceanic currents. From the ADT and oceanic current monthly climatologies, it is shown that there is an annual intrusion of CW with an inward incursion that starts in spring, peaks in the summer, reaches to 28∘ N and 90.45∘ W, and then retreats in winter to approximately 26.5 ∘ N and 88.3 ∘ W. Minimum surface Chl a concentrations (< 0.08 mg m⁻³) are found during the summer–autumn period inside the region of maximum incursion of CW; the opposite is observed during the winter period when Chl a concentrations were at a maximum, e.g., > 0.14 mg m⁻³. The 3-year running averages of the ADT 40 cm isoline qualitatively reproduce the climatological pattern of 25 years showing that before 2002 CW was less intrusive. This suggests that from 2003 onward, larger volumes of oligotrophic waters from the Caribbean Sea have invaded the western GoM and reduced mean surface Chl a concentrations. A direct comparison between the 1998–2002 and 2009–2014 periods indicates that in the latter time interval, the Chl a concentration above waters deeper than 250 m has decreased significantly.